Roscoe Riley Rules : Never Glue your friends to chairs - Applegate, Katherine; Biggs, Brian (New York : Scholastic Inc., 2010)
Roscoe Riley, upset with the notion that his teacher could get in trouble, comes up with a plan to keep the bee antennae on the first graders' heads, and help the drummers stay in their seats for the open house play.
3-6.
Keywords: Glue -- Fiction; Humorous stories; Schools -- Fiction; Helping behavior -- Fiction; Humorous fiction